Simulated Phishing Attack and Forensic Analysis Using the D4I Framework: A Case Study on Kredivo - Muhammad Yusuf Halim; Toto Raharjo; Rosi Rahmadi Syahputra; Erika Ramadhani (Universitas Dinamika, 2025)
Phishing is a form of cyberattack where attackers deceive users into revealing sensitive information such as credentials or financial data, often through fake communication channels or websites. This threat is particularly critical in the financial technology (fintech) sector, where services rely heavily on digital transactions and user trust. This study presents a simulated phishing case targeting Kredivo users to evaluate the effectiveness of the Digital Forensics framework for Reviewing and Investigating cyber-attacks (D4I) in digital forensic analysis. The Cyber Kill Chain (CKC) model was employed to trace attacker behavior across seven phases, from weaponization to actions on objectives. Forensic data was acquired using MOBILedit Forensic Express from two smartphones, namely an iPhone 11 (iOS 15.8.1) and a Vivo Y21 (Android 8.1.0), which served as simulated evidence devices. Using the D4I framework, the investigation successfully identified and correlated key digital artifacts such as phishing links, OTP transmissions, and unauthorized access logs. These findings were organized into a visual chain of artifacts to reconstruct the full attack lifecycle. The results demonstrate that the D4I framework is effective in guiding structured forensic investigations and understanding attack patterns, supporting the enhancement of fintech security strategies.